Influência do tratamento periodontal sobre os níveis da proteína c-reativa ultrassensível em pacientes com insuficiência renal crônica em fase de prétransplante - Amorim, Adriana Gomes (2012)
The present study evaluated the influence of non-surgical periodontal treatment on the levels of C- reactive protein (hsCRP) in patients with chronic renal failure (CRF) in pretransplant. We conducted a controlled and randomized trial to evaluate the periodontal condition and plasma concentrations of hsCRP, albumin and transferrin in 56 dialysis patients divided into two groups: experimental and control. The study was conducted at the dental clinic of Family and Community Health s Unit (USFC), located in Onofre Lopes University Hospital (HUOL), Federal University of Rio Grande do Norte (UFRN), from December 2010 to November 2011. Severe periodontitis was the type of periodontal disease more common, affecting 78.6% of patients. Periodontal conditions, evaluated through the means of probing depth, clinical attachment level, bleeding index and plaque index, proved to be uniform for both groups at the initial examination. There were no differences in levels of inflammatory markers between the two groups. The analysis of the concentrations of hsCRP allowed classifying study participants as at high risk of developing cardiovascular disease. After completion of periodontal treatment in the experimental group, there was a statistically significant reduction of the mean of all periodontal parameters assessed; however this improvement of periodontal health was not accompanied by changes in the levels of hsCRP, albumin and transferrin in the evaluation time. Given this, the periodontal treatment did not promote the reduction of systemic inflammatory burden and risk of cardiovascular complications in patients with CRF